2008
DOI: 10.1021/la800716r
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Monolayers of Alkylphosphonic Acid on GaN Substrates

Abstract: In this paper we describe the formation and characterization of self-assembled monolayers of octadecylphosphonic acid (ODPA) on epitaxial (0001) GaN films on sapphire. By immersing the substrate in its toluene solution, ODPA strongly adsorbed onto UV/O 3-treated GaN to give a hydrophobic surface. Spectroscopic ellipsometry verified the formation of a well-packed monolayer of ODPA on the GaN substrate. In contrast, adsorption of other primarily substituted hydrocarbons (C n H 2 n+1 X; n = 16-18; X = -COOH, -NH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 47 publications
10
86
0
1
Order By: Relevance
“…A series of ellipsometric spectra on each gallium substrate were recorded before and after UV/ozone treatment and upon subsequent RX adsorption as follows. 17 An ellipsometric spectrum of a freshly-prepared gallium substrate prior to UV/ozone treatment (untreated Ga) was first recorded, and was used as a spectrum of an underlying substrate. Then, a spectrum was recorded for the same substrate after UV/ozone treatment (UV-Ga) to obtain the thickness of a surface oxide layer.…”
Section: Spectroscopic Ellipsometrymentioning
confidence: 99%
See 1 more Smart Citation
“…A series of ellipsometric spectra on each gallium substrate were recorded before and after UV/ozone treatment and upon subsequent RX adsorption as follows. 17 An ellipsometric spectrum of a freshly-prepared gallium substrate prior to UV/ozone treatment (untreated Ga) was first recorded, and was used as a spectrum of an underlying substrate. Then, a spectrum was recorded for the same substrate after UV/ozone treatment (UV-Ga) to obtain the thickness of a surface oxide layer.…”
Section: Spectroscopic Ellipsometrymentioning
confidence: 99%
“…CV measurements were carried out in an acetonitrile solution containing 0.1 M TBAPF 6 , because the adsorbed organic layers gradually desorbed from solid gallium substrates in an aqueous solution ( Figure 11) as observed on GaN and AlGaN substrates for ODPA monolayers. 17,18,24 The surface oxide and adsorbed organic layers were assessed based on anodic and cathodic voltage limit (electrochemical potential window) obtained from CV data. However, the electrochemical potential window of ODPA/Ga was much narrower than that of ODPA/UV-Ga (see Figure 12b) probably due to the low ODPA coverage as suggested by the smaller θ water (Table 2; vide supra).…”
Section: Electrochemical Characterization Of Solid Gallium Surfacesmentioning
confidence: 99%
“…Phosphonic acid and its derivatives have been used to passivate the surface of GaN in previous work. 20 The advantage of using these adsorbates for attachment is the ability to customize the side and end groups along the carbon backbone of the phosphonic acid chain. The presence of certain groups provides the capability of altering numerous surface properties.…”
Section: Adsorbate Choicesmentioning
confidence: 99%
“…19 Self-assembled molecules of alkylphosphonic acid are also shown to readily form monolayers on the GaN films. 20 All these reports have demonstrated the potential opportunities offered by terminating the surface of GaN with different chemistries. However, with regards to processing, there remains a significant amount of improvement before industrial application is feasible.…”
Section: Introductionmentioning
confidence: 98%
“…They showed the stability against warm nitric acid of ODP/Al SAM to be the most stable followed by PFDP/AS, DP/Al, PFMS/Al, and OP/Al SAM. Ito et al prepared octadecylphosphonic acid (ODPA) on GaN substrates and characterized them from the viewpoint of chemical stability [34]. They showed that as-prepared ODPA monolayers were desorbed from the GaN substrate by soaking in an aqueous solution, whereas ODPA monolayers heated at 160 o exhibited suppressed desorption in acidic and neutral aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%